(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
The article describes the mechanism of implementation of innovative processes inbusiness entities and foreign experiences, and gives a brief description of the main toolsused in it. In the conclusion, proposals were developed on the feasibility of their use inlocal practice.